Coal and Coke Based Reduction of Vanadium Titanomagenetite Concentrate by the Addition of Calcium Carbonate. (17th February 2021) - Li, Xiaohui; Kou, Jue; Sun, Tichang; Guo, Xiaoshaung; Tian, Yuechao
ABSTRACT: Effects of different coals and coke on the direct reduction of vanadium titanomagnetite concentrate (VTC) added with calcium carbonate were investigated. Lignite was found to provide a better reduction effect than bituminous coal, coke or anthracite, mainly because the gasification reactivity of lignite was obviously better than that of other three reductants, and the metallization degree could reach 95.11 wt% when used lignite. Coals and coke showed little influence on the existence form of Ti in the reduction product, where Ti existed mainly as calcium titanate. Additionally, lignite, coke or anthracite all promoted the growth of metallic iron and calcium titanate particles batter than bituminous coal, which were conducive to subsequent magnetic separation. However, the use of coke or anthracite gave lower purity calcium titanate because of the existence of unreduced iron. Furthermore, these reductants caused large amounts of FeS around metallic iron particles, which hindered the further reduction of iron.